Asymptomatic Paget's bone disease in ethnic Thais: A series of four case reports and a review of the literature - Vorachai Sirikulchayanonta (2018)
Paget's bone disease is quite common in some parts of Europe and countries inhabited by European emigrants, but it is rare in Asia. There have been only 13 reported cases in Southeast Asia, including one reported case from Thailand. Half of the previously reported cases had bone symptoms and the other half were asymptomatic, but were incidentally discovered when patients were being investigated for other medical problems. Here are reported cases of four asymptomatic patients who presented elevation of serum alkaline phosphatase during routine annual medical checkups. All patients were of Chinese descent and all cases were proven by biopsy. Based on this experience, we are of the opinion that a substantial number of unrecognized cases of Paget's disease exist among ethnic Thais. We feel that they would be revealed if clinicians were alerted of its presence and if they included it as a possible diagnosis together with metastasis and osteoporosis when examining bone lesions or when results for elevated serum alkaline phosphatase are detected during routine checkups. We also anticipate that a higher prevalence of this disease may occur in future Thai generations due to the addition of offspring from Asian-European intermarriages to offspring of Chinese descent in the ethnic Thai population. © The Japanese Society for Bone and Mineral Research and Springer 2011.